2017
DOI: 10.1002/ijc.30914
|View full text |Cite
|
Sign up to set email alerts
|

The risk of preterm birth and growth restriction in pregnancy after cancer

Abstract: It is unclear whether cancer and its treatments increase the risk of adverse pregnancy outcomes. Our aim was to examine whether cancer survivors have higher risks of poor outcomes in pregnancies conceived after diagnosis than women without cancer, and whether these risks differ by cancer type and race. Diagnoses from cancer registries were linked to pregnancy outcomes from birth certificates in three U.S. states. Analyses were limited to the first, live singleton birth conceived after diagnosis. Births to wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
41
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 31 publications
12
41
3
2
Order By: Relevance
“…Compared to women with ER‐negative tumors, those with ER‐positive tumors had a lower cumulative incidence at 5 years, but not at 10 years, after diagnosis. After accounting for maternal age and other risk factors, we observed modest increases in preterm birth and low birth weight among births to women with invasive breast cancer relative to the noncancer comparison cohort, consistent with previous reports of women who conceived after a breast cancer diagnosis …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Compared to women with ER‐negative tumors, those with ER‐positive tumors had a lower cumulative incidence at 5 years, but not at 10 years, after diagnosis. After accounting for maternal age and other risk factors, we observed modest increases in preterm birth and low birth weight among births to women with invasive breast cancer relative to the noncancer comparison cohort, consistent with previous reports of women who conceived after a breast cancer diagnosis …”
Section: Discussionsupporting
confidence: 90%
“…Previous U.S.‐based studies have suggested that low birth weight and preterm deliveries are more common among breast cancer survivors relative to the general population . However, among women who conceive after diagnosis, the magnitude of these associations appears to be modest.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…As in previous studies, we found survivors to have a significantly increased risk for preterm delivery compared to comparison subjects. We also found a 45% higher risk for overall hospitalization among survivors compared to population comparisons but could not identify any specific reasons for the increased risk for hospitalization as most survivors belonged to the category hospitalization for other reasons than vaginal bleeding, pre‐eclampsia or threatened preterm labor.…”
Section: Discussionsupporting
confidence: 87%